Real-World Safety and Efficacy of 156 U – 195 U OnabotulinumtoxinA in Adults With Chronic Migraine: Results From the REPOSE Study - Fayyaz Ahmed; Charly Gaul; Katja Kollewe; Ritu C. Singh; Katherine Sommer (BMC Neurology)
Abstract Background The phase 3 PREEMPT clinical trials confirmed the efficacy and safety of 155 U – 195 U onabotulinumtoxinA for individuals with chronic migraine (CM) and is the licensed dose in Canada and Europe. This analysis aimed to analyze the efficacy and safety parameters of 155 U – 195 U onabotulinumtoxinA in participants with CM from the real-world REPOSE study. Methods REPOSE (NCT01686581) was a 2-year, prospective, observational, noninterventional, open-label study that described the real-world use of onabotulinumtoxinA in adults with CM in Europe. Participants received onabotulinumtoxinA approximately every 12 weeks and were monitored for 24 months after starting treatment. Data on participant-estimated mean headache-day frequency in the last month (MHD), Migraine-Specific Quality of Life Questionnaire (MSQ) scores, and adverse events (AEs) were collected at each treatment visit. Participants in the safety analysis population (those who received at least one dose of onabotulinumtoxinA) were stratified into two groups based on the dosage received at four or more treatment visits: 155 U onabotulinumtoxinA and 156 U – 195 U onabotulinumtoxinA groups. Results A total of 641 participants were enrolled at 77 centers. Of those, 218 participants received 155 U ≥ 4 treatment visits, and 77 participants received 156 U–195 U onabotulinumtoxinA ≥ 4 treatment visits. Between-group baseline characteristics were similar. Reductions from baseline in MHD frequency were observed at both doses (156 U – 195 U range, -8.7 to -14.2 MHDs; 155 U range, -8.2 to -11.9 MHDs). Mean change from baseline in MSQ domain scores improved across administration visits for both 155 U onabotulinumtoxinA and 156 U – 195 U onabotulinumtoxinA groups. Treatment with 156 U – 195 U onabotulinumtoxinA was safe and generally well-tolerated with no new safety signals identified. Adverse drug reactions (ADR) were reported in 51/218 in the 155 U group and 10/77 participants in the 156 U – 195 U group; serious adverse drug reactions were 3/218 and 1/77, respectively. The most frequently reported ADR across both dose groups was eyelid ptosis, followed by neck pain, musculoskeletal stiffness. Conclusions These real-world findings of the safety and efficacy of the 155 U – 195 U onabotulinumtoxinA doses are consistent with data from the PREEMPT clinical trials as a treatment option for CM patients. Trial registration NCT01686581. Name of registry: ClinicalTrials.gov. URL of registry: Date of retrospective registration: September 18, 2012. Date of enrolment of first patient: July 23, 2012.